Peran Guru Dalam Mengatasi Perilaku Bullying Pada Peserta Didik Di SDN 164/II Gapura Suci - Linda Yani; Apdoludin Apdoludin; Zulqoidi R. Habibie (CV. Master Literasi Indonesia, 2025)
This study aims to determine the role of teachers in addressing bullying behavior among students at SDN 164/II Gapura Suci. This research is motivated by the bullying behavior experienced by students in the school environment.This study used a qualitative case study approach, with teachers and students at SDN 164/II Gapura Suci as subjects. In collecting data, the researcher used observation, interviews, and documentation methods. Data analysis techniques used were data reduction, data display, and conclusion drawing. To test the validity of the data, a credibility test was used using the triangulation method.Based on the research results, it can be concluded that several forms of bullying behavior occur at SDN 164/II Gapura Suci: physical bullying, verbal bullying, and psychological bullying. The role of teachers in addressing bullying behavior among students encompasses three main aspects: the teacher as a guide, the teacher as a facilitator, and the teacher as an advisor.